ORIENTASI PROFESI DAN MINI HOSPITAL TOUR SEBAGAI MEDIA EDUKASI ATRAUMATIC CARE UNTUK ANAK PRA SEKOLAH - Nurjanah, Suci; dewi, Berlian Kusuma; lumban Touruan, Sari Artauli; Hardi, Gilar Wisnu Hardi; Efendi, Bachtiar; Prasetyo, Joko; Winani, Winani; Sukoco, Aji (Jurnal Pengabdian kepada Masyarakat (NADIMAS), 2025)
Preschool-aged children are vulnerable to experiencing anxiety and fear toward hospital environments and medical personnel, which can negatively affect their healthcare experiences. This community service program aimed to educate preschool children using an atraumatic care approach through professional orientation activities and a mini hospital tour. The activity was conducted at TK Pembina Indramayu, involving 69 children aged 4–6 years. The methods used included interactive education, role-playing, and a fun simulation of a hospital environment. Pre-test results showed that most children were afraid of doctors and medical tools. However, post-test results indicated a significant decrease in these fears and an increased enthusiasm for learning about medical professions and health equipment. This program proved effective in shaping positive early experiences toward healthcare and can serve as an applicable preventive educational model based on atraumatic care for early childhood education institutions.